Lietuvos Didžiosios Kunigaikštystės viešieji notarai XVI amžiaus kryžkelėse: nuo 1512 metų Europos notariato nuostatų iki Antrojo Lietuvos Statuto - Ilarienė, inga (Vilnius University Open Series, 2024)
The Imperial Notary Ordinance, which began being written in the late fifteenth century, not only further cemented the statements set forth in Ars notariae, but also fundamentally transformed the status of notariat, declaring the notariat a governmental institution. According to the opinion of Notariat experts, this Ordinance that was declared in 1512 is fundamental for having the main professional characteristics of the contemporary Latin notariat. This similarity also outlines the continuity of modern European notariat.Lithuanian society in the beginning of the sixteenth century lived with a notariat that was not fully developed, since, only after receiving the right from the Pope in 1501, public notaries began being nominated in the Vilnius diocese. During the first half of the sixteenth century, the development of notariat was visible particularly in the dioceses of GDL. This was to be expected, knowing that the notariat was established in GDL through the Church. Notariat developed in the secular government only as much as there was cooperation with and participation of diocesal notaries public, by serving in the office of a ruler or a voivod. We can observe a tendency in the beginning of the sixteenth century of secularization of the notaries public – they would switch to service in a purely secular office after leaving the clergy and/or becoming supporters of the Reformation. At the same time, similarly to Poland, in the later half of fifteenth century and onwards, Lithuania saw the rise of notaries with apostolic mandate, which declared the primacy of the Pope’s rule. We think, that the Notary Ordinance of 1512, could have had impact (negative?) to the further development of GDL notariat. Firstly by raising the questions of political loyalty and personal choice in regards to which highest authority to obey – the Pope’s or the emperor’s, ecclesiastical or secular.During research we acknowledge that both the First and the Second Statutes of Lithuania could have been partially influenced by the Notary Ordinance by notaries public participating in their conception. Thanks to them, articles regarding the Roman law have been created. The removal of Latin language as the written language of the courts by the Second Statute was not beneficial to the Roman notariat and a serious challenge to the notaries public and to the further development of notariat in GDL. The New Statute became an opportunity for the secular notariat to form as a legal institute. However, for it to happen there had to be further political decisions in support of it, there had to have been the right conditions and enough time to prepare qualified specialists and for the society to be prepared to trust those specialists.
Keywords: 1512 m. Notariato nuostatai; Reichsnotariatsordnung; LDK viešieji notarai; Ars notariae; Pirmasis Lietuvos Statutas; Antrasis Lietuvos Statutas; lotynų kalba; rusėnų kalba